The Transformation of Islamic Religious Education Based on Artificial Intelligence and Digital Literacy in Building the Spirituality of the Muslim Generation in the Society 5.0 Era - Elihami, Elihami; Mohd. Azis; Mowafg Abrahem Masuwd (Edumaspul: Jurnal Pendidikan, 2025)
The transformation of education in the Society 5.0 era requires the integration of digital technology, Artificial Intelligence (AI), and spiritual values in the learning process. Islamic Religious Education (IRE) is no longer focused solely on the conventional transfer of religious knowledge, but must also be capable of developing a Muslim generation that is adaptive, critical, creative, and spiritually grounded amid the rapid advancement of modern technology. This study aims to analyze the transformation of Islamic Religious Education based on Artificial Intelligence and digital literacy in strengthening the spirituality of the Muslim generation in the Society 5.0 era. This research employs a qualitative approach through library research and conceptual analysis of various scientific literature related to AI, digital literacy, Islamic education, and the development of digital society. The findings reveal that the integration of AI and digital literacy into Islamic Religious Education can enhance learning effectiveness, interactivity, personalization, and broader global access to Islamic education. However, this transformation must remain rooted in Islamic moral values, ethics, and spiritual development to ensure that technology does not diminish the essence of Islamic education itself. Therefore, a transformative Islamic education model is needed to balance technological advancement with character building and students’ spiritual development.